1993
DOI: 10.1111/j.1600-0722.1993.tb01133.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA probe detection of periodontopathogens in advanced periodontitis

Abstract: Species‐specific DNA probes were used to determine the presence of Actinobacillus actinomycetemcomitans (A.a.), Porphyromonas (Bacteroides) gingivalis, Prevotella intermedia, Treponema denticola. Eikenella corrodens, Fusobacterium nucleatum, and Wolinella recta in subgingival plaque from deep pockets/sites of patients with advanced periodontitis. The subjects were 20 patients with severe adult periodontitis, 13 men and 7 women (mean age 45.6 ± 6.7 yr). For each subject, 9–10 subgingival sites with the deepest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
2
20
1
Order By: Relevance
“…gingivalis and F. nucleatum, two common oral pathogens associated with human periodontitis (44) and potent activators of viral reactivation, release the short-chain fatty acid (butyrate) as one of the major by-products into the microenvironment (19), along with other volatile fatty acids (25). Moreover, histone hyperacetylation in T cells has been reported following the exposure of T cells to culture supernatants of P. gingivalis (22).…”
Section: Discussionmentioning
confidence: 99%
“…gingivalis and F. nucleatum, two common oral pathogens associated with human periodontitis (44) and potent activators of viral reactivation, release the short-chain fatty acid (butyrate) as one of the major by-products into the microenvironment (19), along with other volatile fatty acids (25). Moreover, histone hyperacetylation in T cells has been reported following the exposure of T cells to culture supernatants of P. gingivalis (22).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontopathic bacterial pathogens, such as Porphyromonas gingivalis and Fusobacterium nucleatum, play a significant role in producing a variety of virulence factors, like BA, which in high amounts lead to the development of periodontal diseases (Socransky and Haffajee 1991;Soder et al 1993;Teng et al 2002). Previous published works related to our group have shown that BA induces apoptosis in inflamed fibroblasts (Kurita-Ochiai et al 2008), Jurkat T cells (Kurita-Ochiai et al 1997;KuritaOchiai and Ochiai 2010), human peripheral blood mononuclear cells (Kurita-Ochiai et al 1999), WEHI 231 and RAJI B-lymphoma cells (Kurita-Ochiai et al 1998), splenic T cells and B cells (Kurita-Ochiai et al 1997, and murine thymocytes (Kurita-Ochiai et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Severe destructive adult periodontitis is caused by a mixed infection and the combination of certain periodontopathogens, for example, Porphyromonas, Prevotella, and Fusobacterium spp. are important in pathogenesis (2). These bacteria produce a variety of virulence factors, such as proteases, LPS, fimbriae, and butyric acid.…”
mentioning
confidence: 99%